PENGARUH PERKEMBANGAN FINTECH TERHADAP KEMANDIRIAN FINANSIAL USAHA MIKRO DENGAN LITERASI KEUANGAN DAN INKLUSI KEUANGAN SEBAGAI VARIABEL INTERVENING - Siti Nurhalizah Lubis; Nurbaiti Nurbaiti; Siti Aisyah (Jurnal Bina Bangsa Ekonomika, 2023)
The purpose of this study is to determine the influence of fintech development on financial independence in micro-enterprises, with financial literacy and financial inclusion as intermediary variables. This type of research is quantitative descriptive research. This study used primary data by taking data from questionnaires. The sampling technique used in this study is probability sampling, so the sample size used is 385 people using the Cochran formula. Data analysis techniques in this study use Structural Equation Modeling (SEM) using smartPLS to be able to solve problems and assumptions raised in this study and used to test relationships between variables. The results of this study show that Fintech has a positive and significant effect on financial literacy. Fintech does not have a positive and significant influence on financial inclusion. Fintech has a positive and significant influence on financial independence, with financial literacy as an intermediary variable. Fintech has a positive and significant effect on financial independence with financial inclusion as an intermediary variable. Fintech does not have a positive and significant influence on financial independence